Phosphonothioate-Based Hydrogen Sulfide Releasing Reagents: Chemistry and Biological Applications - Kang, Jianming; Neill, Deshka L.; Xian, Ming (Frontiers in Pharmacology, 2017)
Hydrogen sulfide (H2S) is a newly recognized gasotransmitter. Studies have demonstrated that the production of endogenous H2S and the exogenous administration of H2S can regulate many physiological and/or pathological processes. Therefore, H2S releasing agents (also known as H2S donors) are important research tools in advancing our understanding of the biology and clinical potential of H2S. Among currently available donors, GYY4137 is probably the most well-known and has been used in many studies in the past ten years. Recently, a number of GYY4137 derivatives (e.g. phosphonothioate-based compounds) have been developed as H2S donors. In this review, we summarize the development and application of these donors, which include Lawesson’s reagent, substituted phosphorodithioates, cyclic phosphorane analogues, and pH-controlled phosphonamidothioates (JK donors). These donors have advantages such as good water-solubility, slow and controllable H2S release capability, and a variety of reported biological activities. However, it should be noted that the detailed H2S release profiles and byproducts under real biological systems are still unclear for many of these donors. Only after we figure out these unknowns we will see better applications of these donors in H2S research and therapy.